2008
DOI: 10.1002/prot.22055
|View full text |Cite
|
Sign up to set email alerts
|

Improved sequence‐based prediction of protein secondary structures by combining vacuum‐ultraviolet circular dichroism spectroscopy with neural network

Abstract: Synchrotron-radiation vacuum-ultraviolet circular dichroism (VUVCD) spectroscopy can significantly improve the predictive accuracy of the contents and segment numbers of protein secondary structures by extending the short-wavelength limit of the spectra. In the present study, we combined VUVCD spectra down to 160 nm with neural-network (NN) method to improve the sequence-based prediction of protein secondary structures. The secondary structures of 30 target proteins (test set) were assigned into alpha-helices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 39 publications
1
65
0
Order By: Relevance
“…In this analysis, the 3 10 -helix was classified as an unordered structure. The root-mean-square deviation ( δ ) and the Pearson correlation coefficient ( r ) between the X-ray and VUVCD estimates of the secondary structure contents of the reference proteins were 0.058 and 0.85, respectively, confirming the high accuracy of the VUVCD estimation [27]. …”
Section: Methodsmentioning
confidence: 95%
“…In this analysis, the 3 10 -helix was classified as an unordered structure. The root-mean-square deviation ( δ ) and the Pearson correlation coefficient ( r ) between the X-ray and VUVCD estimates of the secondary structure contents of the reference proteins were 0.058 and 0.85, respectively, confirming the high accuracy of the VUVCD estimation [27]. …”
Section: Methodsmentioning
confidence: 95%
“…The computational protocol is described elsewhere. 16 Briefly, we used an NN algorithm that predicts the positions of secondary structures by using evolutionary sequence information based on the position-specific scoring matrices generated by the PSI-BLAST algorithm, 17 referring to the numbers of α-helix and β-strand segments and those of amino acid residues forming α-helix and β-strand structures determined by CD spectroscopy and SELCON3 analyses. Turn and unordered structures estimated by the SELCON3 analysis were classified as coil structures.…”
Section: Predictions Of the Positions Of α-Helices And β-Strandsmentioning
confidence: 99%
“…It is known that the accuracy of the VUVCD-NN combination method is about 75% for 30 reference proteins. 16 3 | RESULTS AND DISCUSSION 3.1 | CD spectra Figure 1 shows the CD spectra of K4-methylated H3 proteins. The CD spectrum of H3K4me0 reproduced from the literature data 9 is also shown.…”
Section: Predictions Of the Positions Of α-Helices And β-Strandsmentioning
confidence: 99%
“…Combinations of SRCD measurements and sequence-based neural network modelling methods have been used to improve the empirical predictions of protein secondary structures (Lees & Janes, 2008 ;Matsuo et al 2008). By providing accurate information on the net amounts of each type of secondary structures as calculated from SRCD spectra to augment the training of a standard neural network for the position-specific prediction of the secondary structure type of each amino acid in a protein, Matsuo et al (2008) found a significant improvement in the prediction of the individual amino acids' secondary structures, when compared the known crystal structure. A similar approach was taken by Lees & Janes (2008), except in the latter case experimental information from both SRCD and FTIR measurements were used to enhance the predictions.…”
Section: Synchrotron Radiation Circular Dichroism and Sequence-based mentioning
confidence: 99%